2016
DOI: 10.1039/c6cp03478k
|View full text |Cite
|
Sign up to set email alerts
|

Autochthonous self-assembly of nature's nanomaterials: green, parsimonious and antibacterial carbon nanofilms on glass

Abstract: The development of thin film coatings has been a very important development in materials science for the modification of native material surface properties. Thin film coatings are enabled through the use of sophisticated instruments and technologies that demand expertise and huge initial and running costs. Nano-thin films are yet a furtherance of thin films which require more expertise and much more sophistication. In this work for the first time we present a one-pot straightforward carbon thin film coating me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The use of isolated carbon nanodots from turmeric smoke to form coatings on glass has been demonstrated previously by our group [10]. The results of the antibio lm coatings formed from a rather simple dip and dry technique con rmed that the smoke extracted carbon nanodots could result in costeffective antibio lm coatings.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The use of isolated carbon nanodots from turmeric smoke to form coatings on glass has been demonstrated previously by our group [10]. The results of the antibio lm coatings formed from a rather simple dip and dry technique con rmed that the smoke extracted carbon nanodots could result in costeffective antibio lm coatings.…”
Section: Discussionmentioning
confidence: 62%
“…Figure 2 SEM micrographs con rmed the presence of 10-24nm sized BRS-CNDs. Earlier reports [10,11] also document the successful extraction of CNDs from soot as well.…”
Section: Characterization Of Turmeric Brs-cndsmentioning
confidence: 81%
“…The slides were retrieved and gently washed to remove the loosely adhering bio lm. Then the glass slides were ooded with 0.1% acridine orange and incubated for 2 min [17]. Then the excess stain was washed off and the slides were air dried.…”
Section: Anti-bio Lm Assaymentioning
confidence: 99%
“…As observed from the results, it was found that fumigation of the explants and pretreatment of the explants in carbon soot solution resulted in excellent surface sterilization. Judy et al, (2016) recently reported the self-assembly of the soot-derived carbon dots onto substrates exposed to them [45]. It is a certain possibility that the carbon coated the explants when immersed in the soot solution and exposed to fumes.…”
Section: Modulus Operandi Of Tur and Br For Explant Surface Sterilizamentioning
confidence: 99%